DENTAL DISEASES AND METHODS OF THEIR PREVENTION - Turayev Alimjan Baxriddinovich (Journals Park Publishing, 2022)
On the enamel floor of the tooth is accompanied by a yellowish-brown stain with pigment, unpleasant odor from the mouth, pain when eating sweet, salty, bitter, cold or hot products.
Keywords: demineralization; decay; hard tissue